Penerapan Logika Fuzzy Mamdani Untuk Menentukan Stok Beras Di Toko Anugrah Jaya Cirendeu Berbasis Web - Achmad Lutfi Fuadi (Institut Sains dan Teknologi Nasional, 2023)
Abstract Rice is a very strategic food ingredient. Rice as a food ingredient is still a basic need, so the need for rice is greater than the need for industrial rice. Compared to other staple foods, national rice consumption is relatively large, so that it can be distributed evenly in sufficient quantities and is affordable by the community, increasing income for rice selling entrepreneurs. In every shop selling rice, of course, there are many problems. The problem that is often experienced is that the amount of availability is insufficient or out of stock. Each shop is definitely required to maintain the availability of sufficient stock so that sales in the store run smoothly, Fuzzy Mamdani is more specific, which means that this method pays more attention to the conditions in each Fuzzy area. So that Fuzzy Mamdani will produce decisions that are faster and more accurate. This study aims to help recommend ordering rice stock so that the stock is always available in sufficient quantities, so as to facilitate sales. Keywords: Determination of Rice Stock, Rice, Fuzzy Mamdani